Pension Reform and Capital Market Development : "Feasibility" and "Impact" Preconditions - Vittas, Dimitri (World Bank, Washington, DC, 2014)
The link between pension reform, and capital market development, has become a perennial question, raised every time the potential benefits, and pre-conditions of pension reform are discussed. The author asks two questions. First, what are the basic "feasibility" pre-conditions for the successful launch of a pension reform program? And second, what are the necessary "impact" pre-conditions for the realization of the potential benefits of funded pension plans for capital market development? His main conclusion is that the feasibility pre-conditions, are not as demanding as is sometimes assumed. In contrast, the impact pre-conditions are more onerous. The most import feasibility pre-condition is a strong, and lasting commitment of the authorities to maintaining macroeconomic, and financial stability, fostering a small core of solvent, and efficient banks, and insurance companies, and creating an effective regulatory, and supervisory agency. Opening the domestic banking, and insurance markets to foreign participation, can easily fulfill the second requirement. The main impact pre-conditions include the attainment of critical mass; the adoption of conducive regulations, especially on pension fund investments; the pursuit of optimizing policies by the pension funds; and, a prevalence of pluralistic structures. The author argues that pension funds are neither necessary, nor sufficient for capital market development. Other forces, such as advances in technology, deregulation, privatization, foreign direct investment, and especially regional, and global economic integration, may be equally important. But pension funds are critical players in "symbiotic" finance, the simultaneous and mutually reinforcing presence of many important elements of modern financial systems. They can support the development of factoring, leasing, and venture capital companies, all of which specialize in financing new, and expanding small firms.